2019
DOI: 10.1002/mbo3.859
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces sp. MUM273b: A mangrove‐derived potential source for antioxidant and UVB radiation protectants

Abstract: Microbial natural products serve as a good source for antioxidants. The mangrove‐derived Streptomyces bacteria have been evidenced to produce antioxidative compounds. This study reports the isolation of Streptomyces sp. MUM273b from mangrove soil that may serve as a promising source of antioxidants and UV‐protective agents. Identification and characterization methods determine that strain MUM273b belongs to the genus Streptomyces. The MUM273b extract exhibits antioxidant activities, including DPPH, ABTS, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 108 publications
1
33
0
Order By: Relevance
“…It is not surprising to find Streptomyces from stressful ecosystem such as mangrove forest, produces secondary metabolites to assist in the defence mechanisms, particularly antioxidants are used to prevent oxidative damage. The antioxidant potential of several mangrove Streptomyces in Malaysia have been reported [27][28][29]. To date, the mangrove forest remains largely an understudied ecosystem with respect to investigating their secondary metabolites which are valuable sources for future development of therapeutics [24].…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising to find Streptomyces from stressful ecosystem such as mangrove forest, produces secondary metabolites to assist in the defence mechanisms, particularly antioxidants are used to prevent oxidative damage. The antioxidant potential of several mangrove Streptomyces in Malaysia have been reported [27][28][29]. To date, the mangrove forest remains largely an understudied ecosystem with respect to investigating their secondary metabolites which are valuable sources for future development of therapeutics [24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated that radical scavengers like vitamin E, in the form of tocopherol and tocotrienol, can protect the glutamate-injured cells from oxidative stress. Other than vitamin E, other sources such as microbial resources were also demonstrating strong antioxidants [116][117][118][119][120][121][122][123][124][125][126] and neuroprotective properties [127][128][129][130][131][132] such as metal chelating and radical scavenging potentials [133][134][135][136][137][138][139][140] . In conclusion, neuronal cell seemed to be the most vulnerable brain cells toward glutamate toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…A further supplement of antioxidants is necessary to alleviate high levels of ROS production in order to prevent deleterious effects on the cells, tissues, and organs which are associated with diseases such as cancer, diabetes, and cardiovascular and neurodegenerative diseases [2]. Other antioxidants are derived from food sources [3,4], plants [5][6][7][8], and microbes [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%